2018
DOI: 10.3390/app8112138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Reduced Effective Active Region Volume on Wavelength-Dependent Efficiency Droop of InGaN-Based Light-Emitting Diodes

Abstract: In this study, wavelength-dependent efficiency droop phenomena in InGaN-based light-emitting diodes (LEDs) by a reduced effective active region volume were investigated. Different effective active region volumes can be extracted from theoretical fitting to the efficiency-versus-current curves of standard high efficiency InGaN near-ultraviolet, blue, and green LEDs. It has been found that the effective volume of the active region reduces more significantly with increasing emission wavelength, resulting in a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A modified ABC model with the consideration of the shrink of InGaN QW is employed in our previous study to investigate the carrier recombination dynamics in InGaN MQWs. IQE can be calculated by [24,25], where I is the current injected into the active region, V active is the physical volume of the active region, and q is the elementary charge. Due to the localized carriers in the potential minima of In-rich InGaN clusters [26][27][28], it is reported that the effective active region volume (V effective ) is smaller than the V active .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified ABC model with the consideration of the shrink of InGaN QW is employed in our previous study to investigate the carrier recombination dynamics in InGaN MQWs. IQE can be calculated by [24,25], where I is the current injected into the active region, V active is the physical volume of the active region, and q is the elementary charge. Due to the localized carriers in the potential minima of In-rich InGaN clusters [26][27][28], it is reported that the effective active region volume (V effective ) is smaller than the V active .…”
Section: Resultsmentioning
confidence: 99%
“…The external quantum efficiency (EQE) is calculated by, where P output and hν are the output power and photonic energy. In our experiment, the light extraction efficiency (LEE) is assumed to be 0.8 for the high-efficiency InGaN LEDs grown on PSS and it has been used in our previous study [24]. Therefore, the IQE can be achieved by considering the LEE as IQE = EQE/LEE.…”
Section: Resultsmentioning
confidence: 99%
“…The assumed value is lower than the values for semipolar devices reported in [32,40]. However, for the modeled structures, Auger recombination has the least influence on laser performance of all recombination processes [41]. For quantum wells with a wide bandgap this process may even be neglected entirely.…”
Section: Diffusion and Recombination Coefficientsmentioning
confidence: 89%
“…This results in the reduction of the effective active volume, which contributes to the radiative recombination of electrons and holes. It has been reported that a reduction in the effective active volume of InGaN MQWs leads to a substantial increase in the efficiency droop [16][17][18][19][20]. Therefore, the influence of the internal electric field on the efficiency droop is expected to be explained by the reduced effective active volume due to the increasing internal field strength.…”
Section: Introductionmentioning
confidence: 99%